Whole‐body dose equivalent including neutrons is similar for 6 MV and 15 MV IMRT, VMAT, and 3D conformal radiotherapy. Issue 3 (21st February 2019) - Hauri, Pascal; Schneider, Uwe
Abstract: Purpose: This study investigates the difference in whole‐body dose equivalent between 6 and 15 MV image‐guided radiotherapy (IGRT) for the treatment of a rhabdomyosarcoma in the prostate. Methods: A previously developed model for stray radiation of the primary beam was improved and used to calculate the photon dose and photon energy in the out‐of‐field region for a radiotherapy patient. The dose calculated by the treatment planning system was fused with the model‐calculated out‐of‐field dose, resulting in a whole‐body photon dose distribution. The peripheral neutron dose equivalent was calculated using an analytical model from the literature. A daily cone beam CT dose was added to the neutron and photon dose equivalents. The calculated 3D dose distributions were compared to independent measurements conducted with thermoluminescence dosimeters and an anthropomorphic phantom. The dose contributions from the IGRT treatments of three different techniques applied with two nominal X‐ray energies were compared using dose equivalent volume histograms (DEVHs). Results: The calculated and measured out‐of‐field whole‐body dose equivalents for the IGRT treatments agreed within (9 ± 10) % (mean and type A SD). The neutron dose equivalent was a minor contribution to the total out‐of‐field dose up to 50 cm from the isocenter. Further from the isocenter, head leakage was dominating inside the patient body, whereas the neutron dose equivalent contribution was important close to the surface. There were small differences between the whole‐body DEVHs of the 6 and 15 MV treatments applied with the same technique, although the single scatter contributions showed large differences. Independent of the beam energy, the out‐of‐field dose of the volumetric‐modulated arc therapy (VMAT) treatment was significantly lower than the dynamic intensity‐modulated radiation therapy (IMRT) treatment. Conclusion: The calculated whole‐body dose helped to understand the importance of the dose contributions in different areas of the patient. Regarding radiation protection of the patient for IGRT treatments, the choice of beam energy is not important, whereas the treatment technique has a large influence on the out‐of‐field dose. If the patient is treated with intensity‐modulated beams, VMAT should be used instead of dynamic IMRT in terms of radiation protection of the patient. In general, the developed models for photon and neutron dose equivalent calculation can be used for any patient geometry, tumor location, and linear accelerator.